Pengaruh Lingkungan Sekolah dan Lingkungan Keluarga terhadap Minat Belajar Siswa Kelas VIII di SMPN 1 Pangkalanbaru (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the influence of the school environment and family environment on the learning interest of 8th-grade students at SMPN 1 Pangkalanbaru. Learning interest plays a crucial role in shaping students' academic performance and motivation. A conducive environment, both at school and at home, is believed to significantly contribute to the development of students' enthusiasm for learning. This research employed a quantitative method with a descriptive approach and utilized multiple regression analysis techniques to test the hypotheses. Data were collected through structured questionnaires distributed to 149 students from the 8th grade. The findings indicate that both the school and family environments have a positive and significant impact on students' interest in learning. The school environment's influence was confirmed by a simple linear regression coefficient of 0.229, while the family environment showed a stronger effect with a regression coefficient of 0.355. When tested simultaneously, both variables contributed to a combined effect on students' learning interest, with an R² value of 0.263, indicating that 26.3% of the variance in learning interest can be explained by these two factors. The remaining 73.7% is influenced by other variables not examined in this study, such as peer influence, personal motivation, teaching methods, and access to learning resources. These results underscore the importance of providing a supportive and engaging environment at both school and home to enhance students’ academic motivation. It is recommended that schools foster a positive atmosphere through effective teacher-student interactions, while families are encouraged to actively support their children's learning routines and emotional well-being. Further research is needed to explore other contributing factors and to develop holistic strategies that promote learning interest among junior high school students.